Community Structure and Distribution Patterns of Fish Caught in the Maro River Area, Merauke District - Sianturi, Reny; Amir, Astaman (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
A river basin is a unified water resources management area in one or more river basins. The Maro River is an example of a river in the administrative area of Merauke Regency and is an economically important fish commodity fishing area. The aim of this research is to determine the structure of fish communities and distribution patterns of fish caught in the Maro River Basin, Merauke Regency. This research was conducted in May 2021 using a purposive sampling method. Fish samples were taken from fishermen's catches. Then, the caught fish are identified. There were 13 types of fish that were successfully analyzed, including: Channa striata, Oreochromis niloticus, Oreochromis mossambicus, Lates calcalifer, Hexanematichthys sagor, Anabas testudineus, Toxotes chataerus, Plotosus papuensis, Thryssa scratchleyi, Megalops cyprinoides, Kurtus gulliveri, Clarias batracus and Glossogabius sp. The fish community structure in Kwell and Toray villages found that the diversity index was in the medium category with a value in Kwell village of 2.21 and Toray village of 2.06. Meanwhile, the dominance index in both villages has a dominance index (D') in the low category, namely 0.16. Meanwhile, the uniformity index (E') in Kwell and Toray villages is 2.54 and 2.40 respectively, which is in the high category, resulting in a stable community. Furthermore, the distribution pattern of fish in each village has a random and clustered distribution pattern